The affect(s) of literacy learning in the mud. Issue 2 (4th March 2022) - Cole, David R.; Somerville, Margaret
ABSTRACT: This paper draws on the social ecology of Félix Guattari, to suggest that young children learn in complex social and natural situations, in this case 'getting muddy'. The notion of social ecology will be revived in this paper, to ensure that the human social world is embedded in and part of the natural world, with all its complexities, relations and repetitions (re: muddiness). Children learn from their mistakes, from social interaction, due to their instincts, and as part of an evolving situation, much of which is beyond their control, e.g. their attraction to mud. This paper will search for these types of learning(s) in the affect that can be discerned from teaching and learning, and specifically related to 'muddy literacy'. One might call the combined notions that will be put to work in this paper as 'affective literacy', it is an affective literacy fully imbricated in muddy nature. To achieve this, the paper will attend to empirical research in the early childhood context in Australia, that has charted how children learn from inquiry based learning outdoors in mud, pictures of Aboriginal children outside (and a hand), and a mud classroom painting.